As instâncias do silêncio em A Hora da Estrela, de Clarice Lispector - Ribeiro, Érika Cintra (2010)
Our research is centered in A Hora da Estrela(1977), and investigates the language of silence in its relation with character Macabea, who is inscribed in the discourse of a narrator Rodrigo who is also the one responsible for the creation of the character and of the book, and who assumes author s duplicity with Clarice Lispector. In spite of the existing studies about this novel which follow this line of research, such as the ones by Homem (2001) and Lisbôa (2008), here we reflect about the silence from the point of view of what is said, not said, and implicit that is established in Macabea s discourse in her dialogical relation with characters Olímpico and Rodrigo (the narrator and author of the narrative). It is in this context that we come up with the manifestations of silence appearing in the expressions, reproving, punctuations, and paratexts, where the author s silence becomes visible. The theoretical fundaments of this research concentrate on silence built in the discourse level, either in the sense of inaugural language (Orlandi, 1995), or through the discourse clashes among author, narrator, and characters faced with the limits of expression (Bakhtin1998;1999;2000), or through the empty spaces in the interaction between the text and the reader (Iser). The analysis of the confrontations between the diverging points of view of the authors (Clarice Lispector and Rodrigo) and of their creatures (Macabea, Olímpico, Rodrigo) can spread light on the supposed autobiographical identity between the self who lives and the self who writes, due to the silence that operates in this subtle interval of mediation. The metafictional marks in this double-voiced writing Rodrigo/Clarice Lispector also indicate the frontiers between the book and the absence of the book, which is undone along the spaces of what can or cannot be said, projecting a unique reality made of textual silence. Not a mute silence, but one that is open to the possibilities of meaning something. This is a silence in a latent state, preceding word and, at the same time, in need of it to exist